2021
DOI: 10.2196/28273
|View full text |Cite
|
Sign up to set email alerts
|

Improving Physical Activity Levels in Prevocational Students by Student Participation: Protocol for a Cluster Randomized Controlled Trial

Abstract: Background A consistent finding in the literature is the decline in physical activity during adolescence, resulting in activity levels below the recommended guidelines. Therefore, promotion of physical activity is recommended specifically for prevocational students. Objective This protocol paper describes the background and design of a physical activity promotion intervention study in which prevocational students are invited to participate in the design… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
0
0
Order By: Relevance
“…That is in agreement with literature showing that subjects (7-12 years old) with a higher BMI and body mass had lower performances on all tests requiring propulsion, or lifting of the body mass, and endurance (Casajús, Leiva, Villarroya, Legaz, & Moreno, 2007). Similar to the results of this study, the findings of another study confirmed significant differences between girls who are active and passive commuters in the following: standing broad jump, bent arm hang, 10×5 m sprint, plate tapping, sit-ups, and 20-m shuttle run (Van de Kop, Toussaint, Janssen, Busch, & Verhoeff, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…That is in agreement with literature showing that subjects (7-12 years old) with a higher BMI and body mass had lower performances on all tests requiring propulsion, or lifting of the body mass, and endurance (Casajús, Leiva, Villarroya, Legaz, & Moreno, 2007). Similar to the results of this study, the findings of another study confirmed significant differences between girls who are active and passive commuters in the following: standing broad jump, bent arm hang, 10×5 m sprint, plate tapping, sit-ups, and 20-m shuttle run (Van de Kop, Toussaint, Janssen, Busch, & Verhoeff, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…[ 1 ] Decreasing the level of physical activity among adolescents is a growing problem that increases the risk of health problems for the rest of life. [ 2 ] About 81% of adolescents (11–17years old) are insufficiently physically active globally. [ 3 ] In a study in Iran, the prevalence of physical activity recommended by the World Health Organization among high school students is approximately 27.8%, about 72.2% of whom were not physically active, and the girl’s physical activity was lower than boys’.…”
Section: Introductionmentioning
confidence: 99%